1968
DOI: 10.1139/b68-135
|View full text |Cite
|
Sign up to set email alerts
|

On some relationships between Avena sativa and A. fatua (Gramineae) as studied from Canadian material

Abstract: Many authorities consider that Avena sativa and A. fatua constitute a single species. This attitude is based mainly on morphology, because of the existence of different intermediate forms, and partly on the belief that A. sativa is a product of selection by man from A. fatua. More recently, because of the absence of chromosomal differentiation cytogeneticists have tended to support this contention that A. sativa and A. fatua constitute a single species. This paper reports the discovery of two new characters ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1969
1969
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Yet despite these similarities, this study has also highlighted several features of genome organisation (e.g., the Type II translocation) that show this accession of A. fatua to be genetically distinct from the other hexaploids studied. If the Type II translocation is found to be conserved in other A. fatua accessions then, from a taxonomic perspective, this information combined with more traditional morphological evidence adds further support to the recommendation by Baum (1968) that the full specific status of A. fatua is valid and should be retained.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Yet despite these similarities, this study has also highlighted several features of genome organisation (e.g., the Type II translocation) that show this accession of A. fatua to be genetically distinct from the other hexaploids studied. If the Type II translocation is found to be conserved in other A. fatua accessions then, from a taxonomic perspective, this information combined with more traditional morphological evidence adds further support to the recommendation by Baum (1968) that the full specific status of A. fatua is valid and should be retained.…”
Section: Resultsmentioning
confidence: 65%
“…Second, the hybridisation of this tetraploid with a third diploid species to form a triploid, which then underwent a second cycle of chromosome doubling to produce the hexaploid (Thomas 1992). Based on a similar genomic composition and the observation that all hexaploid taxa are interfertile, it has been suggested that they may all belong to a single biological species (Ladizinsky and Zohary 1971), although Baum (1968) concluded that A. sativa and A. fatua deserved the rank of species based on detailed morphological analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The variable colours of the seeds of A. fatua can be contrasted with the yellowish-white seeds of A. sativa, and the characteristic seed dormancy of A. fatua with near absence of dormancy in the cultivar. Baum (1968) was cited on less visible differences in the lodicules and epiblasts. The lodicule of A. sativa is distinguished by an attached side lobe, which is absent in A. fatua.…”
Section: Description and Account Of Variationmentioning
confidence: 99%
“…The lodicule of the cultivated oats is of the Sativa-type (Baum, 1968). Only a very small number of lodicules were of the Fatua-type and were interpreted as A. sativa X fatua (or sterilis) F1 hybrids or F1-like phenotypes (Baum, 1968, and1969a). The great majority of lodicules in the 5000 samples were of the Sativatype.…”
Section: The Paleamentioning
confidence: 99%